After the crisis: German R&D-intensive industries in a good position - Heike Belitz; Marius Clemens; Martin Gornig; Florian Mölders; Alexander Schiersch; Dieter Schumacher (DIW Economic Bulletin, 2011)
The strong reliance of the German economy on the industry sector has been a point of criticism for years now. Germany is too strongly focused on export, making it susceptible to crises and fluctuations in demand and exchange rates, the critics allege. A non-critical look at the numbers during the recent economic crisis seems to reaffirm these old concerns: Industrial productivity shrank significantly and exports collapsed. Taking a closer look, however, it is clear that R&D-intensive industries passed their trial by fire during the crisis. The joint strategy of companies, unions and politicians managed to keep employment figures mostly stable during the global slump in demand and thus helped these industries to be well prepared for the upswing with a broad portfolio consisting of vehicle manufacturing, machine building, and electronic, measurement and medical technology. Looking specifically at the emerging markets, these industries did better than just defend their leading positions; they expanded market shares during the crisis. This can be seen in the international comparison of the latest data on value added, productivity and bilateral trade, conducted by DIW Berlin. The results: The R&D-intensive industries in Germany have already returned to their long-run growth path and are in a favorable position for the future.
Keywords: F14; O14; O57; 330; industrial specialization; international trade; manufacturing industries